Catalytic Synthesis of the Iso-octyl Palmitate from Palmitic Acid and Isooctanol with Water-Tolerant Solid Acid - Chen, L.J.; Shi, H.X. (Asian Journal of Chemistry, 2011)
Iso-octyl palmitate is synthesized via esterification of palmitic acid and isooctanol when the water-tolerant solid acid is used as the catalyst. The particular chelate molecular structure of SnC2O4 makes Sn atom have the suitable acid intensity. The steric hindrance in the course of the reaction is reduced because of its molecular structure with the plane surface. In addition, the stability of molecule of SnC2O4 is strengthened because of its chelate molecular structure. All these factors lead to its high catalytic activity in the esterification reaction. Many factors, which have an effect on the yield of iso-octyl palmitate, have been studied. The reaction conditions for synthesizing iso-octyl palmitate with high yield are optimized with the orthogonal experiment. The optimum conditions for synthesizing iso-octyl palmitate with high yield are as follows: reaction time is 2.5 h and the mol ratio of isooctanol to palmitic acid is 1.8:1 and the dosage of the catalyst is 2.0 % and the reaction temperature is 150 ºC.